POTRET KONSEP DIRI MAHASISWA JPOK FKIP UNLAM DAN HUBUNGANNYA DENGAN PRESTASI AKADEMIK - Warni, Herita (Multilateral Jurnal Penjas Or, 2012)
Abstract: Learning situation is complex and involves the interaction of the various components. In JPOK FKIP UNLAM particularly on physical, healthy and recreation education program, many students are unable to be consistent maintaining their academic g achievement on each semester which finally results on the increase of their study term. Academic achievement primarily is the result of interaction from various factors among students. One of the factors that affects isself-concept possessed by students.This study aimed to capture the level of student self-concept as well as identifying the relationship between the sef-concept and students’ academic achievement by using correlative descriptive research design. This research uses 113 people as sample. The technique of determining the number of sample used a probability sampling method. The research instrument used questionnaires of self-concept. The questionnaire consisted of self-image, self-ideal, self-esteem, role and identity. Academic achievement was measured from the cumulative index achievement of the students in the second semester. The results showed most students have a good self-concept (n = 100; 88%). Data analysis using Pearson correlation test shows that the self-concept and students’ academic achievement have no sufficiently closed relationship with r = 0207 and α = 0.028 but has included significant. A positive sign figures out that there is a linear relationship. The better self-concept owned by the students, the better achievement will be achieved by the students. So the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. Keywords: self-concept, learning/academic achievement Abstrak: Situasi belajar bersifat kompleks dan melibatkan interaksi dari berbagai komponen. Di JPOK FKIP Unlam khususnya pada program studi Penjaskesrek banyak mahasiswa yang tidak mampu menjaga prestasi belajar/akademik pada setiap semster yang berdampak pada bertambahnya masa studi sehingga tida bisa menyelesaikan studi pada tepat waktunnya. Prestasi belajar akademik pada dasarnya merupakan hasil interaksi dari berbagai faktor yang berbeda antara satu mahasiswa dengan mahasiswa lain. Salah satu faktor yang mempengaruhi tersebut adalah konsep diri yang dimiliki mahasiswa. Penelitian ini bertujuan untuk memotret tingkat konsep diri mahasiswa dan sekaligus mengidentifikasi hubungan konsep diri dengan prestasi belajar/akademik mahasiswa dengan menggunakan desain penelitian deskriptif korelatif. Sampel penelitian ini sebanyak 113 orang. Teknik penentuan jumlah sampel dengan dengan metode probability sampling. Instrumen penelitian menggunakan kuesioner konsep diri. Kuesioner konsep diri terdiri dari gambaran diri, ideal diri, harga diri, peran, dan identitas diri. Alat ukur prestasi akademik dilihat dari nilai indeks prestasi kumulatif mahasiswa pada semester II. Hasil penelitian menunjukkan sebagian besar mahasiswa memiliki konsep diri baik sebesar (n= 100;88% ). Analisa data menggunakan uji korelasi Pearson menunjukkan hasil bahwa antara konsep diri dengan prestasi belajar/akademik mahasiswa terdapat hubungan tidak cukup erat dengan r=0.207 dan α=0,028 tetapi sudah termasuk signifikan. Tanda positif menggambarkan bahwa terjadi